Comparative transcriptome analysis between long- and short-term survival after pig-to-monkey cardiac xenotransplantation reveals differential heart failure development - Lim, Byeonghwi; Jang, Min-Jae; Oh, Seung-Mi; No, Jin Gu; Lee, Jungjae; Kim, Sang Eun; Ock, Sun A.; Yun, Ik Jin; Kim, Junseok; Chee, Hyun Keun; Kim, Wan Seop; Kang, Hee Jung; et al. (Animal cells and systems, 2023)
Cardiac xenotransplantation is the potential treatment for end-stage heart failure, but the allogenic organ supply needs to catch up to clinical demand. Therefore, genetically-modified porcine heart xenotransplantation could be a potential alternative. So far, pig-to-monkey heart xenografts have been studied using multi-transgenic pigs, indicating various survival periods. However, functional mechanisms based on survival period-related gene expression are unclear. This study aimed to identify the differential mechanisms between pig-to-monkey post-xenotransplantation long- and short-term survivals. Heterotopic abdominal transplantation was performed using a donor CD46-expressing GTKO pig and a recipient cynomolgus monkey. RNA-seq was performed using samples from POD60 XH from monkey and NH from age-matched pigs, D35 and D95. Gene-annotated DEGs for POD60 XH were compared with those for POD9 XH (Park et al. 2021). DEGs were identified by comparing gene expression levels in POD60 XH versus either D35 or D95 NH. 1,804 and 1,655 DEGs were identified in POD60 XH versus D35 NH and POD60 XH versus D95 NH, respectively. Overlapped 1,148 DEGs were annotated and compared with 1,348 DEGs for POD9 XH. Transcriptomic features for heart failure and inhibition of T cell activation were observed in both long (POD60)- and short (POD9)-term survived monkeys. Only short-term survived monkey showed heart remodeling and regeneration features, while long-term survived monkey indicated multi-organ failure by neural and hormonal signaling as well as suppression of B cell activation. Our results reveal differential heart failure development and survival at the transcriptome level and suggest candidate genes for specific signals to control adverse cardiac xenotransplantation effects.